Hospital, Employment, and Price Indicators for the Health Care Industry: Second Quarter 1997 - Sensenig, Arthur L. (CENTERS for MEDICARE & MEDICAID SERVICES, 1997)
This regular feature of the journal includes a discussion of recent trends in health care spending, employment, and prices. The statistics presented in this article are valuable in their own right and for understanding the relationship between the health care sector and the overall economy. In addition, they allow us to anticipate the direction and magnitude of health care cost changes prior to the availability of more comprehensive data.